A study on the prediction of bond strength of ambient cured geopolymer concrete - Rakesh, Padakanti; Rao, S. Venkateswara; Pancharathi, Rathish Kumar (Journal of Structural Engineering, 2024)
Owing to the strict provisions in implementing novel concrete like geopolymer concrete for construction applications,it is imperative that the development of the concrete and its properties there of takes priority. In the present work atthe outset aggregate optimization based on particle packing theory (MTM and JDD) is taken up to develop the GPC.Then the prediction of the bond performance of such a sustainable concrete is attempted. The study compares the bondperformance of geopolymer concrete based on numerical simulation of pull-out test as per IS 2770 Part-1 with varyingembedment lengths and diameter of the reinforcement bar for different grades of Geopolymer concrete. Simulation ofthe beam-end pullout test is attempted with parameters including embedment length to rebar diameter ratio, concretecover to rebar diameter ratio for grades of geopolymer concrete and an analytical equation to predict bond strengthof geopolymer concrete is proposed. It was concluded from the studies on bond performance of geopolymer that thebond stress has an inverse relationship with embedment length, direct relationship with concrete cover, and grade ofconcrete. whereas, the change in diameter of the rebar has no significant effect on the bond performance of geopolymerconcrete. The proposed analytical equation is found to yield satisfactory results in predicting the bond strength basedon numerical simulation.